Factors associated with adherence to the COVID-19 vaccine in pregnant women - Patrícia Pereira Vasconcelos; Ana Catarina Torres de Lacerda; Cleide Maria Pontes; Tatiane Gomes Guedes; Luciana Pedrosa Leal; Sheyla Costa de Oliveira (Universidade de São Paulo, 2024)
Objective: to identify factors associated with adherence to the COVID-19 vaccine during pregnancy. Method: cross-sectional and analytical study with 348 postpartum women in shared accommodation at the Municipal Maternities of Recife-PE. Data was collected through interviews during the months of June to September 2022. Pearson's Chi-Square or Fisher's Exact tests and the Poisson regression model were applied for statistical analysis. Results: 17.2% of pregnant women adhered to the complete vaccination schedule, and adherence was associated with access to the internet/TV/radio (p-value = 0.011), routine prenatal vaccination (p-value = 0.019), safety of the efficacy of the COVID-19 vaccine and partner support (p-value = 0.020). Postpartum women without access to the internet/TV/radio, and who feel confident about the effectiveness of the vaccine, had higher prevalence rates for adhering to COVID-19 vaccination, with PRs of 2.56 and 3.25, respectively. Conclusion: there was evidence of low adherence to the vaccination schedule against COVID-19 during the gestational period, considering the number of recommended doses and the interval between them. Therefore, professionals in their clinical practice must make pregnant women aware of the importance of immunization and compliance with the vaccination schedule.